Wavelet Analysis of Resultant Velocity Belonging to Genuine and Forged Signatures - Syed Ahmad S.M.; Loo L.Y.; Wan Adnan W.A.; Md. Anwar R. (Blackwell Publishing Inc., 2023)
adult; analysis of variance; article; decomposition; discrete wavelet transform; forensic science; human; perception; wavelet analysis